2016
DOI: 10.2147/prbm.s96384
|View full text |Cite
|
Sign up to set email alerts
|

Fear of failure among a sample of Jordanian undergraduate students

Abstract: BackgroundFear of failure (FoF) is the motivation to avoid failure in achievement tests, and involves cognitive, behavioral, and emotional experiences.AimsThe primary purpose of this study was to determine the level of FoF among students at The Hashemite University, Jordan. We were also interested in identifying the difference in the level of FoF between the sexes, the academic level, and grade-point average (GPA).MethodA total of 548 students participated in the study by completing the Performance Failure App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…The psychometric qualities of the PFAI scales have been examined in a great number of studies, in Jordan for instance by Alkhazaleh &Mahasneh, 2016 andin Turkish by Khahraman &Sungur, 2016 and they have demonstrated strong internal consistency. The short version of the PFAI that included 5 items (items: 7, 8, 11, 19, 24) was demonstrated to be also a valid and reliable measure of fear of failure.…”
Section: Trait Fearmentioning
confidence: 99%
“…The psychometric qualities of the PFAI scales have been examined in a great number of studies, in Jordan for instance by Alkhazaleh &Mahasneh, 2016 andin Turkish by Khahraman &Sungur, 2016 and they have demonstrated strong internal consistency. The short version of the PFAI that included 5 items (items: 7, 8, 11, 19, 24) was demonstrated to be also a valid and reliable measure of fear of failure.…”
Section: Trait Fearmentioning
confidence: 99%
“…It should also be noted that the PFAI, originally designed for North American sports, has been validated in different languages and countries, including the British [31], Spanish [7], Chinese [32], Portuguese [33,34,35], and Danish [36] contexts, and recently for Turkish [37] and Jordanian [38] conditions, as well as in education with Spanish secondary school students in physical education classes [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Related research showed that girls often believe that failures indicate incompetence, are insurmountable and that they will continue to occur, no matter what effort they may make in the future, and with as many past successful experiences as they may have had. In other words this greater fear of failure that girls experience translates more easily into poor performance [30,31,32]. In a way, this is quite absurd since the results of our research showed the opposite: girls performed better than boys in both situations, either they had attended urban or rural primary schools.…”
Section: Average Performance Of Students Coming From Urban Schools Bamentioning
confidence: 55%